Utilization of Silk Waste and Standard Requirements for their Recycling - Abdumanabovich, Sulaymanov Sharif; o‘g‘li, Maxmudov Umidjon Bahodir; Muxtaraliyevich, Turdialiyev Umid (American Journal of Biodiversity, 2025)
This scientific paper analyzes the types of silk waste and the standards applied in their recycling process. Adhering to the standards for waste generated in sorting and silk reeling sections helps to improve product quality.